2006
DOI: 10.1111/j.1365-2958.2006.05263.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Nostoc punctiforme akinete‐expressed genes using differential display

Abstract: SummaryAkinetes are spore-like resting cells formed by certain filamentous cyanobacteria that have increased resistance to environmental stress. They can be found at low frequencies in dense cultures experiencing low light or phosphate limitation, but also form at high frequencies in a zwf mutant strain of Nostoc punctiforme following dark incubation in the presence of fructose. The wild-type strain is capable of facultative heterotrophic growth under these conditions and does not form akinetes. To identify ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 46 publications
1
15
0
1
Order By: Relevance
“…Here, we showed that low light was the best inducer of akinete formation in Anabaena variabilis and confirmed the earlier finding (Argueta & Summers, 2005;Argueta et al, 2006) that phosphate starvation was the best inducer in N. punctiforme. The different inducing conditions also had an effect on the time course of akinete development.…”
Section: Triggers Of Akinete Differentiationsupporting
confidence: 79%
See 1 more Smart Citation
“…Here, we showed that low light was the best inducer of akinete formation in Anabaena variabilis and confirmed the earlier finding (Argueta & Summers, 2005;Argueta et al, 2006) that phosphate starvation was the best inducer in N. punctiforme. The different inducing conditions also had an effect on the time course of akinete development.…”
Section: Triggers Of Akinete Differentiationsupporting
confidence: 79%
“…However, only a few genes involved in akinete formation have been so far identified (e.g. Argueta et al, 2006;Campbell et al, 1996;Leganés et al, 1994Leganés et al, , 1998Lehner et al, 2011;Zhou & Wolk, 2002; see also review by Maldener et al, 2014). Microarray analysis of a zwf mutant of N. punctiforme that is able to differentiate akinetes with similar phenotype characteristics to WT akinetes in a few days (Argueta & Summers, 2005) revealed the upregulation of 255 genes, 41 % of which encode known proteins (Campbell et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…RNA was isolated (Argueta et al, 2006) from exponentially growing NA1000 and SM921 in M2G broth. 59 RACE was performed as described by Argueta et al (2006).…”
Section: Methodsmentioning
confidence: 99%
“…RNA was isolated (Argueta et al, 2006) from exponentially growing NA1000 and SM921 in M2G broth. 59 RACE was performed as described by Argueta et al (2006). The following ctrA-specific primers were used: 59 RACE CtrA Rev, 59-CCGCAGGGTGCGCAGAACATCGAT-39; 59 RACE CtrA Nested Rev, 59-GCAGGATAAGATCGTAGTCGTAGAT-39.…”
Section: Methodsmentioning
confidence: 99%
“…The RNA (3 mg) was treated with DNase, and cleaned using RNA Clean & Concentrate (Zymo Research). RNA quality was checked by measuring the A 260 /A 280 ratio and running an RNA sample on a 0.8 % agarose gel (Argueta et al, 2006). Preparation of cDNA.…”
Section: [For Cultures Lacking Both Fabh and (P)ppgpp] And 1610mentioning
confidence: 99%